2022
DOI: 10.21037/atm-22-5969
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of essential trace elements in chronic kidney disease: a narrative review

Abstract: Background and Objective: Chronic kidney disease (CKD) is an important public health concern.With the decline of renal function, CKD patients gradually progress to end-stage kidney disease and need to undergo dialysis or kidney transplantation to maintain life, bringing a heavy economic burden to the family and society. Therefore, it is necessary to effectively prevent and delay the progression of CKD. Essential trace elements play an indispensable role in CKD, and the objective of this study is to systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 232 publications
(265 reference statements)
1
6
0
Order By: Relevance
“…(2020), Mn contributes to the development of glomerular disease. However, the observed increase in circulating Mn levels may be due to the gradual aggravation of chronic renal failure with time (Xie et al, 2022). The results from the present study are supportive of a protective effect by Mn against CKDu, within the observed range of concentrations.…”
Section: Data Synthesissupporting
confidence: 80%
“…(2020), Mn contributes to the development of glomerular disease. However, the observed increase in circulating Mn levels may be due to the gradual aggravation of chronic renal failure with time (Xie et al, 2022). The results from the present study are supportive of a protective effect by Mn against CKDu, within the observed range of concentrations.…”
Section: Data Synthesissupporting
confidence: 80%
“…This risk is compounded by heightened hepcidin production, which can hasten iron absorption. Furthermore, the chronic inflammatory state characteristic of CKD may further disrupt iron metabolism, exacerbating the potential for complications [151]. The interplay between iron supplementation, altered iron metabolism and the inflammatory state in CKD can create a complex scenario where microbial proliferation and susceptibility to infections may be heightened.…”
Section: Iron (Fe)mentioning
confidence: 99%
“…Copper (Cu) is the body's third most abundant trace element [151]. Copper is an important enzymatic cofactor for energy production and iron absorption.…”
Section: Copper (Cu)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients undergoing HD have been reported to have a higher mortality rate than the general population did [1]. Iron is an essential element in most human cells and a cofactor for vital proteins and enzymes [2]. Iron dysregulation is common in patients undergoing HD.…”
Section: Introductionmentioning
confidence: 99%